Industrial Conflicts Scenario in India - Bhat, Archana; Swami, Ravikant (Prabandhan: Indian Journal of Management, 2015)
The present study endeavoured to find out the trend of industrial conflicts in India due to changes in composition and structure base after the initiation of the economic reforms. The study is primarily based upon secondary data and found that number of work disputes, mandays lost, and workers' involvement in disputes showed a gradual decline over the period of time. The numbers of workers involved in strikes were more than the number of workers involved in lockouts; also, the mandays lost in lockouts were more than the mandays lost in strikes. The number of disputes in the public as well as private sector also depicted sluggish fluctuations and growth, although there were more disputes in the private sector than in the public sector. Indiscipline and violence were found to be the significant causes of industrial disputes. Production losses due to disputes were higher in the private sector than in the public sector. The study concluded that economic reforms have shifted the power in the hands of the employees.